The association of OPG polymorphisms with risk of osteoporotic fractures: A systematic review and meta-analysis. Issue 31 (6th August 2021) - Ding, Jianfeng; Zhang, Chongyang; Guo, Yuning
Abstract: Background: Subjects with low bone mineral density and osteoporosis are more likely to suffer osteoporotic fractures during their lifetime. Polymorphisms in osteoprotegerin (OPG) gene are found to be associated with low bone mineral density and osteoporosis risk but their association with fracture risk is inconclusive. Here, we performed a meta-analysis to investigate the relationship between OPG polymorphisms with susceptibility to osteoporotic fractures. Methods: Eligible studies investigating the association between common OPG polymorphisms (A164G, T245G, T950C, and G1181C) and risk of osteoporotic fracture were retrieved from PubMed, EMBASE, Web of Science, and the Cochrane Library. Odds ratio (OR) and the 95% confidence interval (CI) were calculated in the allelic, dominant, recessive, and homozygous model. Subgroup analyses of vertebral fractures, Caucasians, and postmenopausal women were also performed. Results: A total of 14 studies comprising 5459 fracture cases and 9860 non-fracture controls were included. A163G was associated with fracture risk in dominant (OR = 1.29, 95%CI 1.11–1.50), recessive (OR = 1.64, 95%CI 1.10–2.44), and homozygous model (OR = 1.73, 95%CI 1.16–2.59). T245G was significantly correlated with susceptibility to fractures in all genetic models. Subjects with CC genotype of T950C had a reduced risk of fracture compared to those with CT or TT genotypes (OR = 0.81, 95%CI 0.70–0.94, P = .004). Subgroup analysis showed that A163G and T245G but not T950C and G1181C were associated with vertebral fracture risk. Conclusion: OPG A163G and T245G polymorphisms were risk factors of osteoporotic fractures while T950C had a protective role. These polymorphisms can be used as predictive markers of fractures.